THE IMPACT OF CULTURE IN SHAPING ESG DISCLOSURE: A SYSTEMATIC REVIEW OF MULTINATIONAL PRACTICES - Uswatun Hasanah; Tri Jatmiko Wahyu Prabowo (Jurnal Bisnis dan Akuntansi, 2024)
The goal of this study is to comprehend how local culture affects ESG (Environmental, Social, and Governance) disclosure and how culture-influenced ESG innovation can enhance corporate sustainability performance. This study uses a systematic literature review (SLR) approach with the PRISMA method to consolidate relevant studies related to the impact of culture on ESG disclosure. The results show that local culture influences ESG disclosure through social and ethical values. Aligning ESG innovation with culture and institutional support enhances sustainability performance, thereby enhancing the effectiveness of the contextual ESG framework in achieving corporate sustainability. This study emphasizes the importance of a local, culture-based ESG framework and encourages the integration of cultural values in ESG reporting and innovation to support global sustainability. This research offers a new perspective on the impact of local culture on ESG transparency, enriching the literature with a cultural approach to build a more inclusive ESG framework